2013
DOI: 10.1016/j.neuron.2013.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Not So Uncertain at Last: Locus Coeruleus and Decision Making

Abstract: A report by Payzan-LeNestour et al. (2013) in this issue of Neuron shows that the human locus coeruleus, a brain stem nucleus containing cell bodies of noradrenergic neurons, dynamically tracks the level of uncertainty about knowledge of the environment while making decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…However, Yu and Dayan (2005) proposed a different, complementary role of ACh and NE, in which only expected uncertainty, linked to the known stochasticity (lack of reliability) of a predictive relationship, is coded by ACh. NE, on the other hand, tracks unexpected uncertainty; that is, the actual, important changes in the regularities governing the relationships in the world (Duzel & Guitart-Masip, 2013; Payzan-LeNestour, Dunne, Bossaerts, & O’Doherty, 2013). A context-dependent modulation of the balance between these two must ensure that learning is enabled when learning is due (for actual changes).…”
Section: Neurobiological Underpinningsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Yu and Dayan (2005) proposed a different, complementary role of ACh and NE, in which only expected uncertainty, linked to the known stochasticity (lack of reliability) of a predictive relationship, is coded by ACh. NE, on the other hand, tracks unexpected uncertainty; that is, the actual, important changes in the regularities governing the relationships in the world (Duzel & Guitart-Masip, 2013; Payzan-LeNestour, Dunne, Bossaerts, & O’Doherty, 2013). A context-dependent modulation of the balance between these two must ensure that learning is enabled when learning is due (for actual changes).…”
Section: Neurobiological Underpinningsmentioning
confidence: 99%
“…relationships in the world (Duzel & Guitart-Masip, 2013;Payzan-LeNestour, Dunne, Bossaerts, & O'Doherty, 2013). A contextdependent modulation of the balance between these two must ensure that learning is enabled when learning is due (for actual changes).…”
Section: Precision Regulationmentioning
confidence: 99%
“…A similar reciprocal influence exists between the LC and motor activity. A theoretical framework was established in the last decade, proposing that the phasic activity of LC is an interrupt signal that represents “unexpected uncertainty”, and, in turn, modulates sensorimotor transformation [ 130 , 131 , 132 ]. This process may be the foundation of various forms of adaptive behaviors.…”
Section: Lc Modulates Sensorimotor Transformationmentioning
confidence: 99%
“…Physiologically, regulation of arousal and autonomic function is related to the activity of the locus coeruleus norepinephrine (LC‐NE) and basal forebrain cholinergic (BF‐Ch) systems (Aston‐Jones & Cohen, 2005; Benarroch, 2009, 2021; Berridge, 2008; Everitt & Robbins, 1997; Liebe et al, 2022; Sara, 2009). The LC‐NE activity plays an important role in enhancing the processing of information salience (Vazey et al, 2018; Wang & Munoz, 2015) and has been shown to have an influence on decision making (de Gee et al, 2017; Duzel & Guitart‐Masip, 2013). BF‐Ch activity is a key component in promoting sensory perception (Pinto et al, 2013) and in emotion regulation (Ballinger et al, 2016; Bentley et al, 2003a, 2003b; McGaugh, 2004; Picciottoet al, 2012).…”
Section: Introductionmentioning
confidence: 99%